The ISLAMIC Banks and its ability to exceed The world Finanical Crisis 2008 (Islamic Dubi Bank) - العبيدي, نهاد عبد الكريم; صبر, اركان بدران (Journal of Economics and Administrative Sciences, 2013)
The Recent days witness an in creasing importanc of Islamic Banks which stems from the wide spread in Islamic and non-Islamic countries,Especially in USA and European countries.the consideration in Islamic Banks came after the financial crisis in 2008.Islamic Banks work with conventional banks in most countries,that is,the formers may face the same risks which face the latters,that represent the larger percent of the International Banking system.the problms that may affect Islamic Banks related to many causes,some related to the working in common economic environment.others related to the possibility of simulation to the method of investment and financing in conventional Banks,this mean,the work with principles not compling with Islamic laws(sharaah).the purpos of this study is to shed alight on the transaction mechanism in Islamic banking system which anabled islamic banks to overcom the international financial crisis in 2008,besides it is cabability to manag it is found in away lessening the degree of risk.So the study confains three Articals,the first one deals with the theoritcal framework of Islamic Banking,the second one is devoted to study the conceptual and causal framework of iternational financial crisis in 2008,while the latter article deals with the how Dubai Islamic Bank was affected by this crisis.